2015
DOI: 10.1007/s11926-015-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Therapies, Approved and Emerging: a Review of Infectious Risk and Prevention During Use

Abstract: The development of B cell-targeted biologics represents a major advance in the treatment of autoimmune rheumatic diseases. As with other immunosuppressive agents, risk of infection is a key clinical concern. This review summarises safety data from 15 years of experience of rituximab in autoimmune diseases with a particular focus on opportunistic infection and class-specific complications and infection risk. Rarely, cases of progressive multifocal leucoencephalopathy in rituximab-treated patients (5/100 000) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
14
0
1
Order By: Relevance
“…However lupus patients may be at increased risk of developing PML compared to other rheumatic diseases (312). The risk of rituximab causing PML in rheumatic diseases including rheumatoid arthritis and SLE has been estimated at 5/100,000 which is less than the risk observed with some other immunosuppressants in other diseases (313).…”
Section: Rituximab For Refractory Moderate Lupusmentioning
confidence: 99%
“…However lupus patients may be at increased risk of developing PML compared to other rheumatic diseases (312). The risk of rituximab causing PML in rheumatic diseases including rheumatoid arthritis and SLE has been estimated at 5/100,000 which is less than the risk observed with some other immunosuppressants in other diseases (313).…”
Section: Rituximab For Refractory Moderate Lupusmentioning
confidence: 99%
“…Despite the failure of randomized controlled trials (RCTs) in meeting their primary end points in systemic lupus erythematosus (SLE) , primary Sjögren's syndrome (SS) and inflammatory myopathies , RTX is commonly used off‐label in these indications and other various rheumatic and musculoskeletal diseases (RMDs), often in cases that are refractory to other systemic therapies . However, the immunomodulatory properties of biologic disease‐modifying antirheumatic drugs (bDMARDs) in general, including RTX, have raised safety concerns, prompting careful evaluation in RCTs and intensive surveillance after marketing . Data from RCTs and long‐term extension (LTE) studies of RTX in various RMDs have shown no major safety signals .…”
Section: Introductionmentioning
confidence: 99%
“…RA-ILD is the second most common cause of mortality in RA [2]. The high mortality has been attributed to uncontrolled systemic inflammatory disease, infections and complication from therapies [3,4]. While the treatment of RA has greatly improved in recent years with the introduction of biologic therapies, the use of such agents has often been restricted in RA-ILD due to concerns over safety.…”
Section: Introductionmentioning
confidence: 99%